Diagnosis Kondisi Minyak Tranformator Menggunakan Teknik Dissolved Gas Analysis - Fauzia Haz; Muhammad Rizki Akbar; Giri Angga Setia (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2022)
At the Cikalong hydropower plant there are 3 power transformers with a voltage rating of 6.3/77 kV, because of their long life, it is necessary to analyze the condition of the transformer oil. One way to determine the level of fault gas contained in transformer oil is the DGA (Dissolved Gas Analysis) test. DGA will extract the gas to find out indications of disturbance based on the interpretation of the dissolved gases data, namely the Total Dissolved Combustible Gas (TDCG), Key Gas, Roger's Ratio, Doernenberg's Ratio and Duval's Triangle methods. This method is in order to determine the condition of the transformer oil is normal or not, measure the breakdown voltage value and calculate the correlation value between operating hours and the amount of power production. The results of the DGA analysis on transformer units 1, 2, and 3 of the Cikalong hydropower sub-unit show the TDCG value in condition 1, which includes all transformers in good condition. The value of the correlation coefficient between hours of operation and the number of kWh production with TDCG is 0.267 and 0.297, respectively, which indicates the relationship between these variables is a weak relationship (standard value is close to 1).